IMPLEMENTATION OF COMMUNITY NURSING CARE FOR HYPERTENSION AT THE KEDAI DURIAN PUBLIC HEALTH CENTER, MEDAN JOHOR DISTRICT NORTH SUMATERA PROVINCE IN 2025 - Sanni Sihombing; Samrotul Fuadah Al-Ansoriyani; Sri Murtini; Pardosi, Yuen Natrisia; Manullang, Putri Margaretha; Gita Lestari; Indira Virli Ananda, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Hypertension is a global health burden, defined as blood pressure 140/90 mmHg by WHO. Global prevalence reaches 22%, with North Sumatra showing a high prevalence of 29.19%, yet medical diagnosis remains low. At Kedai Durian Health Center, 416 cases were recorded by April 2025. Objective: This study aims to provide comprehensive nursing care to elderly individuals with hypertension in the Kedai Durian Health Center service area, Medan Johor. Methods: A descriptive case study approach was utilized, following the nursing process: assessment, diagnosis, intervention planning, implementation, and evaluation. Results: The intervention led to an increase in the elderly’s knowledge regarding hypertension management, although the clinical problem was not fully resolved during the study period. Conclusion: Strengthening primary health care through the nursing process is essential for hypertension control in the elderly, specifically in improving health literacy.